Odpowiedź :
Odpowiedź:
3-2x= 1-4x
-2x +4x= 1 -3
2x= -2 /:2
x= - 1
5x-4 =3x+2
5x-3x= 2+4
2x= 6 /:2
x=3
7x-3 = 2x+2
7x-2x= 2+3
5x= 5 /:5
x=1
x-3 = 3x +4
x-3x= 4 +3
-2x= 7/*(-1)
2x= - 7/:2
x= - 3 i 1/2
Szczegółowe wyjaśnienie:
Cześć!
Szczegółowe wyjaśnienie:
a)
[tex]3 - 2x = 1 - 4x = \\ - 2x + 4x = 1 - 3 \\ 2x = - 2 \\ x = - 1[/tex]
b)
[tex]5x - 4 = 3x + 2 = \\ 5x - 3x = 2 + 4 \\ 2x = 6 | \div 2 \\ x = 3 [/tex]
c)
[tex]7x -3 = 2x + 2 = \\ 7x - 2x = 2 + 3 \\ 5x = 5 \\ x = 1[/tex]
d)
[tex]x - 3 = 3x + 4 \\ x - 3x = 4 + 3 = \\ - 2x = 7 = \\ x = - \frac{7}{2} [/tex]